2015
DOI: 10.1007/s12665-015-4681-3
|View full text |Cite
|
Sign up to set email alerts
|

Acidification of shallow groundwater in the unconfined sandy aquifer of the city of Douala, Cameroon, Western Africa: implications for groundwater quality and use

Abstract: The alluvial aquifer underlying the city of Douala comprises shallow Quaternary deposits where groundwater is the main source for domestic and drinking purposes. Shallow groundwater in the area show signs of acidification with average pH range of 3.8-6.8. Long-term groundwater chemistry data (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013), hydrogeochemical and R mode factor analysis were used to establish the acidification process of shallow groundwater and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Few studies have been carried out [19]- [24] and established the level of nitrate concentration in shallow groundwater is up to 160 mg/l. These studies show the nitrate to be of anthropogenic origins.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been carried out [19]- [24] and established the level of nitrate concentration in shallow groundwater is up to 160 mg/l. These studies show the nitrate to be of anthropogenic origins.…”
Section: Nomentioning
confidence: 99%
“…The Bependa district presents a wider range of pH-values ( Figure 5) and the most acidic sample being BE 12 (pH = 3.5) while Logpom pH-value distribution is narrow (4.6 -5.3) and relatively close to the input function (5.5 -5.8) [23]. [24] showed that the acidity of groundwater in Quaternary alluvium of Douala may have resulted from origins such as; acid rain, coastal atmospheric deposition, anthropogenic activities and cation exchange from marine sodium with Figure 6 is a display of the EC which gives the total ion content of water samples [39]. It shows a higher and wider range (332 -1646 µS/cm) in Bependa than in Ndogbong (103 -483 µS/cm), Logpom (42 -250 µS/cm) and Ndogpassi (2 -57.5 µS/cm).…”
Section: Phmentioning
confidence: 99%
“…Studies of groundwater quality across Africa are numerous, and include rural (Grimason et al, 2013), urban (Mangore andTaigbenu, 2004) and peri-urban (Mokuolu et al, 2017), as well as agricultural (Esterhuizen et al, 2014), industrial (Takem et al, 2015) and domestic (Vala et al, 2011) studies. Most of these studies reveal decreases in groundwater quality related to human activities at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Alkalinity indicates the ability for groundwater to neutralize the inputs of acidity, and generally consists of the bicarbonate (HCO 3 ) and the carbonate (CO 3 2− ) concentration. High alkalinity values might lead to a high buffering capacity [30]. [33].…”
Section: Discussionmentioning
confidence: 99%